Does growth restriction increase the vulnerability to acute ventilation-induced brain injury in newborn lambs? Implications for future health and disease. (9th August 2017) - Allison, B. J.; Hooper, S. B.; Coia, E.; Jenkin, G.; Malhotra, A.; Zahra, V.; Sehgal, A.; Kluckow, M.; Gill, A. W.; Yawno, T.; Polglase, G. R.; Castillo-Melendez, M.; et al.
Abstract : Fetal growth restriction (FGR) and preterm birth are frequent co-morbidities, both are independent risks for brain injury. However, few studies have examined the mechanisms by which preterm FGR increases the risk of adverse neurological outcomes. We aimed to determine the effects of prematurity and mechanical ventilation (VENT) on the brain of FGR and appropriately grown (AG, control) lambs. We hypothesized that FGR preterm lambs are more vulnerable to ventilation-induced acute brain injury. FGR was surgically induced in fetal sheep (0.7 gestation) by ligation of a single umbilical artery. After 4 weeks, preterm lambs were euthanized at delivery or delivered and ventilated for 2 h before euthanasia. Brains and cerebrospinal fluid (CSF) were collected for analysis of molecular and structural indices of early brain injury. FGRVENT lambs had increased oxidative cell damage and brain injury marker S100B levels compared with all other groups. Mechanical ventilation increased inflammatory marker IL-8 within the brain of FGRVENT and AGVENT lambs. Abnormalities in the neurovascular unit and increased blood–brain barrier permeability were observed in FGRVENT lambs, as well as an altered density of vascular tight junctions markers. FGR and AG preterm lambs have different responses to acute injurious mechanical ventilation, changes which appear to have been developmentally programmed in utero .